Research in Digital Design and Test at Tallinn University of Technology - Raimund, Ubar; Gert, Jervan; Artur, Jutman; Jaan, Raik; Peeter, Ellervee; Margus, Kruus (ХНУРЭ, 2008)
An overview about the recent research results at the Tallinn University of Technology in the field of digital design and test is presented. The main topics discussed in the paper cover digital design, verification, emulation, dependability, fault simulation, and test generation. An experimental research environment is described which consists of prototype tools developed as a side-effect of our research activities. This environment together with a set of dedicated elearning tools serves also for teaching purposes for the disciplines of design and test of embedded systems.
Keywords: digital design; verification